2021
DOI: 10.1111/jhn.12883
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status and its dietary and lifestyle factors in children during the first 5 years of life: A cross‐sectional multicentre Jiangsu bone study

Abstract: Background To explore the vitamin D status with its demographic and lifestyle factors including dietary, supplementation, and physical activity in 0–5 years old children. Methods This was a large population‐based cross‐sectional multicentre study in which the children were recruited from 12 Children’s Health Care Centers by a stratified cluster random‐sampling method in 10 cities in Jiangsu Province, China. Results A total number of 5289 children were investigated. The prevalence of vitamin D deficiency was 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Valtuerna et al [78] and Zhao et al [79], evaluated the factors associated with vitamin D deficiency in adolescents and preschool children and found out that sleep duration was one of the most relevant factors associated with vitamin D serum levels. Valtuerna et al [78] examined 1006 European adolescents (aged 12.5-17.5 years) in a multicenter study measuring body composition, biochemical marker, socioeconomical status, dietary intake, physical activity, fitness, sleep time, and vitamin D genetic polymorphism in a stepwise multivariate linear regression analysis stratified by gender.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Valtuerna et al [78] and Zhao et al [79], evaluated the factors associated with vitamin D deficiency in adolescents and preschool children and found out that sleep duration was one of the most relevant factors associated with vitamin D serum levels. Valtuerna et al [78] examined 1006 European adolescents (aged 12.5-17.5 years) in a multicenter study measuring body composition, biochemical marker, socioeconomical status, dietary intake, physical activity, fitness, sleep time, and vitamin D genetic polymorphism in a stepwise multivariate linear regression analysis stratified by gender.…”
Section: Resultsmentioning
confidence: 99%
“…In the Jiangsu Bone Health Study, Zhao et al [79] assessed the vitamin D status with its demographic and lifestyle factors in 5289 children during the first 5 years of life in a population-based cross-sectional multicenter study in China. The prevalence of vitamin D deficiency was 30.1%.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the exposure levels of MPA, other factors were also associated with the variance of 25(OH)D, including age, sex, season at measurement, glucocorticoid daily dose, and use of vitamin D 3 supplements and VDRAs. Age and glucocorticoid daily dose were negatively associated with 25(OH)D, while male sex, summer [9,[36][37][38]. One large population-based multicenter study in Jiangsu Province of China investigated 5289 children and revealed that children of older age and being a girl were at a higher risk of vitamin D deficiency [36].…”
Section: Discussionmentioning
confidence: 99%
“…Age and glucocorticoid daily dose were negatively associated with 25(OH)D, while male sex, summer [9,[36][37][38]. One large population-based multicenter study in Jiangsu Province of China investigated 5289 children and revealed that children of older age and being a girl were at a higher risk of vitamin D deficiency [36]. In our study, boys with SLE had about fivefold higher 25(OH)D levels than girls with SLE (B = 5.958, P \ 0.001) and increased age was associated with decreased 25(OH)D concentrations (B = -0.959, P \ 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Although some journals can specialise in a particular area (e.g., the Journal of Parenteral and Enteral Nutrition, or Alimentary Pharmacology and Therapeutics), JHND must navigate through much broader waters and consider research from all points in our discipline. As such, we bring together quantitative 20,21 and qualitative 22,23 research that can have direct clinical practice implications, or which is more suited to a purely academic audience. We are the official journal of the British Dietetic Association and we take particular pride in publishing the work of practising clinicians.…”
mentioning
confidence: 99%